2019
DOI: 10.1080/10803548.2019.1598123
|View full text |Cite
|
Sign up to set email alerts
|

Occupational accidents in Swedish construction trades

Abstract: The purpose of this study is to analyze accidents occurring in the Swedish construction industry, focusing specifically on the situation in the individual trades. The article includes all occupational accidents with at least 1 day of absence from work that were reported to the Swedish Social Insurance Agency for the year 2016. The results, focusing on accident cause, injured body parts as well as accidents per weekday, month and age, show that although the trades share commonalities regarding occupational acci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In this context, there are many studies showing that work accidents are most common in the 25-44 age range and least common in the 65+ age range [12,13,[29][30][31]. In some studies, the 16-24 age range was found to be the age group where work accidents occurred most frequently [26,32]. There are also studies indicating that the 35-45 age range is the age group that most frequently experiences fatal work accidents [28].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, there are many studies showing that work accidents are most common in the 25-44 age range and least common in the 65+ age range [12,13,[29][30][31]. In some studies, the 16-24 age range was found to be the age group where work accidents occurred most frequently [26,32]. There are also studies indicating that the 35-45 age range is the age group that most frequently experiences fatal work accidents [28].…”
Section: Discussionmentioning
confidence: 99%
“…Reference Purpose Difference Berglund et al, 2019 [24] The author analyzed fatalities and injuries according to daily, monthly, and workers' ages in 2016 in Spain. This study analyzes 18 accident types considering several weather conditions.…”
Section: Research Related To the Causes Of Construction Disastersmentioning
confidence: 99%
“…As indicated in Table 1 , previous research in this area falls into three categories: (i) research related to the causes of construction disasters [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], (ii) research related to an analysis of the weather impact on injury and fatal accidents in construction [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , ...…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, occupation is a potent factor for worker health encompassing both occupational and socioeconomic conditions playing a crucial role for differences in sick leave (Lidwall et al 2018;Mastekaasa 2005;Virtanen et al 2010). As employers have a key role in addressing preventive work environment measures, branches are also crucial for the identification of where to intervene (Berglund et al 2019;Gaspar et al 2018;Irastorza et al 2016;Kristman et al 2016;Marshall et al 1997). Branch is also an important contextual factor constituting economic conditions and future prospects influencing wages, job opportunities and job security (Irastorza et al 2016;Kristman et al 2016;Marshall et al 1997;Virtanen et al 2010).…”
Section: Occupational Working Conditions and The Contextual Factor Ofmentioning
confidence: 99%